The Two Sets of DMSO Respiratory Systems of Shewanella piezotolerans WP3 Are Involved in Deep Sea Environmental Adaptation - Xiong, Lei; Jian, Huahua; Zhang, Yuxia; Xiao, Xiang (Frontiers in Microbiology, 2016)
Dimethyl sulfoxide (DMSO) is an abundant methylated sulfur compound in deep sea ecosystems. However, the mechanism underlying DMSO-induced reduction in benthic microorganisms is unknown. Shewanella piezotolerans WP3, which was isolated from a west Pacific deep sea sediment, can utilize DMSO as the terminal electron acceptor. In this study, two putative dms gene clusters [type I (dmsEFA1B1G1H1) and type II (dmsA2B2G2H2)] were identified in the WP3 genome. Genetic and physiological analyses demonstrated that both dms gene clusters were functional and the transcription of both gene clusters was affected by changes in pressure and temperature. Notably, the type I system is essential for WP3 to thrive under in situ conditions (4°C/20 MPa), whereas the type II system is more important under high-pressure or low-temperature conditions (20°C/20 MPa, 4°C/0.1 MPa). Additionally, DMSO-dependent growth conferred by the presence of both dms gene clusters was much higher than growth conferred by either of the dms gene clusters alone. These data collectively suggest that the possession of two sets of DMSO respiratory systems is an adaptive strategy for WP3 survival in deep sea environments. We propose, for the first time, that deep sea microorganisms might be involved in global DMSO/DMS cycling.